2021
DOI: 10.1136/jmedgenet-2020-107471
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of protein-truncating and missense variants in PALB2 in 15 768 women from Malaysia and Singapore

Abstract: BackgroundRare protein-truncating variants (PTVs) in partner and localiser of BRCA2 (PALB2) confer increased risk to breast cancer, but relatively few studies have reported the prevalence in South-East Asian populations. Here, we describe the prevalence of rare variants in PALB2 in a population-based study of 7840 breast cancer cases and 7928 healthy Chinese, Malay and Indian women from Malaysia and Singapore, and describe the functional impact of germline missense variants identified in this population.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
1
2
1
Order By: Relevance
“…In this study, the frequency of PALB2 pathogenic variants was 1.3% (3/225) among patients aged ≤ 30 years, similar to that of 1%–1.85% in previous studies involving the Chinese (Zhou et al 2020 ), Malaysian, and Singaporean populations (Ng et al 2022 ). Additionally, we observed an approximately 2-fold occurrence of PALB2 pathogenic variants in breast cancer patients aged ≤ 30 years compared to those aged 31-40 years (1.3% vs 0.68%), however, the difference was not statistically significant ( p = 0.398).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, the frequency of PALB2 pathogenic variants was 1.3% (3/225) among patients aged ≤ 30 years, similar to that of 1%–1.85% in previous studies involving the Chinese (Zhou et al 2020 ), Malaysian, and Singaporean populations (Ng et al 2022 ). Additionally, we observed an approximately 2-fold occurrence of PALB2 pathogenic variants in breast cancer patients aged ≤ 30 years compared to those aged 31-40 years (1.3% vs 0.68%), however, the difference was not statistically significant ( p = 0.398).…”
Section: Discussionsupporting
confidence: 90%
“…These two mutations have been reported as recurrent mutations in unselected breast cancer studies in China (c.2257C>T: 6/16501 and 4/7657, respectively; c.2167_2168del: 12/16501 and 2/7657, respectively) (Deng et al 2019;Zhou et al 2020), however, we identified these mutations only once in each case. Although the PALB2 c.509_510del and c.172_175del were identified as founder or hotspot mutations in European populations (Rogoża-Janiszewska et al 2020), and PALB2 c.2968G>T was found to be a hotspot mutation in women with breast cancer from Malaysia and Singapore, none of these were observed in our study (Ng et al 2022). This highlights the ethnic and regional disparities in the spectrum of PALB2 pathogenic variants.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Similarly, another PALB2 pathogenic variant, c.2323C>T was identified in French-Canadian women in Quebec, where the Q775X mutation occurred in about 0.5% of the women diagnosed for breast cancer [41]. An Asian study identified 0.73% and 0.14% in breast cancer and normal control cohorts, respectively, and the most common recurrent mutations were c.7G>T and c.2968G>T in the cancer cohort [19]. A higher risk of developing breast cancer was estimated in PALB2 mutation carriers, which was 9.1-fold compared to non-carriers in the UK [1].…”
Section: Discussionmentioning
confidence: 95%